2002
DOI: 10.1177/030802260206501005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fatigue Syndrome: An Evaluation of an Occupational Therapy Inpatient Intervention

Abstract: It has been stated that, although most chronic fatigue syndrome (CFS) patients can be treated in primary care and that cognitive behaviour therapy and prescribed, graded aerobic exercise appear to be promising in outpatient management, a minority of patients will require inpatient care (Royal Colleges of Physicians, General Practitioners and Psychiatrists 1996). To date, little has been written on the need for and impact of an inpatient approach for patients with CFS. This study builds on previous work to show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Participants who were trained in activity pacing self-management seemed to have learned superior coping strategies for dealing with limitations in daily life activities or their illness in general compared with control participants, findings that are consistent with those of a similar study (Cox, 2002). Experimental group participants may have reappraised their daily life activities, altering the value they placed on those activities, in turn resulting in improved satisfaction with performance of desired activities (Persson, Andersson, & Eklund, 2011).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Participants who were trained in activity pacing self-management seemed to have learned superior coping strategies for dealing with limitations in daily life activities or their illness in general compared with control participants, findings that are consistent with those of a similar study (Cox, 2002). Experimental group participants may have reappraised their daily life activities, altering the value they placed on those activities, in turn resulting in improved satisfaction with performance of desired activities (Persson, Andersson, & Eklund, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The rationale for activity pacing can be found in several strategies observed in people with CFS: reduced activity levels resulting from and in anticipation of fatigue (Nijs et al, 2011;Vercoulen et al, 1997), lowered activity peaks followed by very long rest periods (van der Werf, Prins, Vercoulen, van der Meer, & Bleijenberg, 2000), and ability to perform short periods of light to moderate activity without exacerbating symptoms (Clapp et al, 1999;Cook et al, 2005). Several randomized controlled trials (RCTs) have shown positive effects of treatment programs based on activity pacing for people with CFS (Cox, 2002;Crawley et al, 2013;Goudsmit et al, 2012;Jason et al, 2013;Pemberton & Cox, 2014;Taylor, 2004). The findings of these studies are in line with those of a pilot study in which several of the current authors participated (Nijs et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Limited evidence supports the responsiveness of the IMQ following a lifestyle management programme [40], but suggests that the CFS-APQ and CFS-SL are not responsive to change in health following exercise programmes [41,42]. Where reported, the statistical significance of score change or between groups difference was described; no study reported the clinical significance of score change or specifically evaluated PROM responsiveness or interpretation of score change.…”
Section: Cfs/me-specific Promsmentioning
confidence: 99%
“…Other types of modified CBT, with occupational therapy/rehabilitation aspects, were examined in one RCT 97 of high quality evidence and two controlled trials in adults 98,99 of low quality evidence. These three studies found significant differences between groups for symptoms (one RCT, one controlled trial), emotional distress (one controlled trial) and global health/ quality of life (3 controlled trials).…”
Section: Main Results For Modified Cognitive Behavioural Therapy (Mcbt)mentioning
confidence: 99%